CN110282964A - Sagger for sintering mullite-cordierite lithium battery cathode material and preparation method thereof - Google Patents

Sagger for sintering mullite-cordierite lithium battery cathode material and preparation method thereof Download PDF

Info

Publication number
CN110282964A
CN110282964A CN201910538109.3A CN201910538109A CN110282964A CN 110282964 A CN110282964 A CN 110282964A CN 201910538109 A CN201910538109 A CN 201910538109A CN 110282964 A CN110282964 A CN 110282964A
Authority
CN
China
Prior art keywords
mullite
cordierite
fine powder
lithium battery
sagger
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Pending
Application number
CN201910538109.3A
Other languages
Chinese (zh)
Inventor
赵惠忠
单峙霖
张寒
李述党
陈建威
马九宏
单文春
王相辉
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Jingzhou Huaxin Mullite Co Ltd
Wuhan University of Science and Technology
Original Assignee
Jingzhou Huaxin Mullite Co Ltd
Wuhan University of Science and Technology
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Jingzhou Huaxin Mullite Co Ltd, Wuhan University of Science and Technology filed Critical Jingzhou Huaxin Mullite Co Ltd
Priority to CN201910538109.3A priority Critical patent/CN110282964A/en
Publication of CN110282964A publication Critical patent/CN110282964A/en
Pending legal-status Critical Current

Links

Classifications

    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B35/00—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
    • C04B35/01—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics
    • C04B35/16—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics based on silicates other than clay
    • C04B35/18—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics based on silicates other than clay rich in aluminium oxide
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B35/00—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
    • C04B35/01—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics
    • C04B35/16—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics based on silicates other than clay
    • C04B35/18—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics based on silicates other than clay rich in aluminium oxide
    • C04B35/185—Mullite 3Al2O3-2SiO2
    • F—MECHANICAL ENGINEERING; LIGHTING; HEATING; WEAPONS; BLASTING
    • F27—FURNACES; KILNS; OVENS; RETORTS
    • F27D—DETAILS OR ACCESSORIES OF FURNACES, KILNS, OVENS OR RETORTS, IN SO FAR AS THEY ARE OF KINDS OCCURRING IN MORE THAN ONE KIND OF FURNACE
    • F27D5/00—Supports, screens or the like for the charge within the furnace
    • F27D5/0006—Composite supporting structures
    • F27D5/0012—Modules of the sagger or setter type; Supports built up from them
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
    • C04B2235/02—Composition of constituents of the starting material or of secondary phases of the final product
    • C04B2235/30—Constituents and secondary phases not being of a fibrous nature
    • C04B2235/32—Metal oxides, mixed metal oxides, or oxide-forming salts thereof, e.g. carbonates, nitrates, (oxy)hydroxides, chlorides
    • C04B2235/3217—Aluminum oxide or oxide forming salts thereof, e.g. bauxite, alpha-alumina
    • C04B2235/3222—Aluminates other than alumino-silicates, e.g. spinel (MgAl2O4)
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
    • C04B2235/02—Composition of constituents of the starting material or of secondary phases of the final product
    • C04B2235/30—Constituents and secondary phases not being of a fibrous nature
    • C04B2235/34—Non-metal oxides, non-metal mixed oxides, or salts thereof that form the non-metal oxides upon heating, e.g. carbonates, nitrates, (oxy)hydroxides, chlorides
    • C04B2235/3427—Silicates other than clay, e.g. water glass
    • C04B2235/3463—Alumino-silicates other than clay, e.g. mullite
    • C04B2235/3481—Alkaline earth metal alumino-silicates other than clay, e.g. cordierite, beryl, micas such as margarite, plagioclase feldspars such as anorthite, zeolites such as chabazite
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
    • C04B2235/02—Composition of constituents of the starting material or of secondary phases of the final product
    • C04B2235/30—Constituents and secondary phases not being of a fibrous nature
    • C04B2235/34—Non-metal oxides, non-metal mixed oxides, or salts thereof that form the non-metal oxides upon heating, e.g. carbonates, nitrates, (oxy)hydroxides, chlorides
    • C04B2235/349—Clays, e.g. bentonites, smectites such as montmorillonite, vermiculites or kaolines, e.g. illite, talc or sepiolite
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
    • C04B2235/70—Aspects relating to sintered or melt-casted ceramic products
    • C04B2235/74—Physical characteristics
    • C04B2235/77—Density
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
    • C04B2235/70—Aspects relating to sintered or melt-casted ceramic products
    • C04B2235/96—Properties of ceramic products, e.g. mechanical properties such as strength, toughness, wear resistance
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
    • C04B2235/70—Aspects relating to sintered or melt-casted ceramic products
    • C04B2235/96—Properties of ceramic products, e.g. mechanical properties such as strength, toughness, wear resistance
    • C04B2235/9669—Resistance against chemicals, e.g. against molten glass or molten salts

Landscapes

  • Engineering & Computer Science (AREA)
  • Chemical & Material Sciences (AREA)
  • Ceramic Engineering (AREA)
  • Manufacturing & Machinery (AREA)
  • Materials Engineering (AREA)
  • Structural Engineering (AREA)
  • Organic Chemistry (AREA)
  • Mechanical Engineering (AREA)
  • General Engineering & Computer Science (AREA)
  • Compositions Of Oxide Ceramics (AREA)

Abstract

本发明涉及一种莫来石‑堇青石质锂电池正极材料烧结用匣钵及其制备方法。其技术方案是:将30~35wt%的莫来石颗粒、20~25wt%的莫来石细粉、30~35wt%的堇青石颗粒、4~7wt%的糊精和5~7wt%广西白泥混合,搅拌,得混合料A;再将30~35wt%的莫来石细粉、30~35wt%的镁铝尖晶石细粉和35~36wt%的红柱石细粉搅拌,烘干,研磨,得混合料B。然后将混合料A置于模具中,在压头表面均匀洒层混合料B,以钵口朝下的方式机压成型,干燥,于1300~1400℃条件下保温5~6小时,制得莫来石‑堇青石质锂电池正极材料烧结用匣钵。本发明成本低廉、工艺简单和成品率高;制备的莫来石‑堇青石质锂电池正极材料烧结用匣钵体积密度大、耐压强度高、抗热震性优良和抗侵蚀性能好。The invention relates to a mullite-cordierite lithium battery anode material sintering sagger and a preparation method thereof. Its technical scheme is: 30-35wt% mullite particles, 20-25wt% mullite fine powder, 30-35wt% cordierite particles, 4-7wt% dextrin and 5-7wt% Guangxi white The mud is mixed and stirred to obtain a mixture A; then 30-35wt% mullite fine powder, 30-35wt% magnesium-aluminum spinel fine powder and 35-36wt% andalusite fine powder are stirred, dried, Grind to obtain mixture B. Then put the mixture A in the mould, sprinkle the layer of mixture B evenly on the surface of the pressure head, machine press it with the mouth of the bowl facing down, dry it, and keep it warm at 1300-1400°C for 5-6 hours to obtain Mo Sagger for sintering the anode material of Lithium-cordierite lithium battery. The invention has the advantages of low cost, simple process and high yield; the prepared mullite-cordierite lithium battery cathode material sagger has a large volume density, high compressive strength, excellent thermal shock resistance and good corrosion resistance.

Description

莫来石-堇青石质锂电池正极材料烧结用匣钵及其制备方法Sagger for sintering mullite-cordierite lithium battery cathode material and preparation method thereof

技术领域technical field

本发明属锂电池正极材料烧结用匣钵技术领域。特别涉及一种莫来石-堇青石质锂电池正极材料烧结用匣钵及其制备方法。The invention belongs to the technical field of saggers for sintering positive electrode materials of lithium batteries. In particular, it relates to a mullite-cordierite lithium battery cathode material sintering sagger and a preparation method thereof.

背景技术Background technique

匣钵作为锂电池正极材料烧结所必须使用的载体,具有抗热震性能好、强度高、抗锂电池正极材料侵蚀性能好等优点,因此,研究锂电池正极材料烧结用匣钵对新能源的发展有着重大的意义,此外,匣钵现阶段难以回收利用,造成了资源的严重浪费,研究可长时间使用匣钵对资源节约具有重要的意义。As a necessary carrier for the sintering of lithium battery positive electrode materials, sagger has the advantages of good thermal shock resistance, high strength, and good corrosion resistance of lithium battery positive electrode materials. Development is of great significance. In addition, saggers are difficult to recycle at this stage, resulting in a serious waste of resources. Research on long-term use of saggers is of great significance to resource conservation.

“一种莫来石泡沫陶瓷及其制备方法”(CN104311117A)专利技术,以糖、铝硅质细粉为原料,利用发泡技术在高温下烧制而成,虽然具有较低成本与高附加值,但是由于材料中所形成的物相单一,导致其热震性能较低。"A kind of mullite foam ceramics and its preparation method" (CN104311117A) patent technology, using sugar, aluminum and silicon fine powder as raw materials, using foaming technology to fire at high temperature, although it has low cost and high additional value, but due to the single phase formed in the material, its thermal shock performance is low.

“一种堇青石蜂窝陶瓷及制备方法”(CN101045629A)专利技术,以LiO2、滑石、煅烧高岭土、氧化铝、氢氧化铝和硅微粉等为原料,通过后混合、练泥、挤出、湿坯切割、干燥、干坯切割、烧成等工艺得到成品,虽有较高的强度,但原料成本过高,难以大规模应用。"A kind of cordierite honeycomb ceramics and its preparation method" (CN101045629A) patented technology, using LiO 2 , talc, calcined kaolin, alumina, aluminum hydroxide and silicon micropowder as raw materials, after mixing, smelting, extruding, wet The finished products are obtained by billet cutting, drying, dry billet cutting, and firing. Although they have high strength, the cost of raw materials is too high and it is difficult to apply them on a large scale.

“一种轻质堇青石-莫来石复合陶瓷材料及其制备方法”(CN103922713A)专利技术,水铝石、无定型二氧化硅、滑石粉和黏土为原料,通过搅拌、成型、干燥后再高温下烧成,虽强度与抗热震性能较好,但由于堇青石易与锂电池正极材料反应,因此材料所体现的抗侵蚀性能较弱和使用寿命低。"A lightweight cordierite-mullite composite ceramic material and its preparation method" (CN103922713A) patent technology, diaspore, amorphous silica, talcum powder and clay as raw materials, after stirring, molding and drying Fired at high temperature, although the strength and thermal shock resistance are good, but because cordierite is easy to react with the positive electrode material of lithium battery, the corrosion resistance of the material is weak and the service life is low.

发明内容Contents of the invention

本发明旨在克服现有技术缺陷,目的是提供一种成本低廉和工艺简单的莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法,用该方法制备的莫来石-堇青石质锂电池正极材料烧结用匣钵抗热震性能好、抗侵蚀性能优异和使用寿命长。The present invention aims to overcome the defects of the prior art, and aims to provide a method for preparing a mullite-cordierite lithium battery cathode material sintering sagger with low cost and simple process, and the mullite-cordierite prepared by the method The sagger used for sintering the positive electrode material of the bluestone lithium battery has good thermal shock resistance, excellent corrosion resistance and long service life.

为实现上述目的,本发明采用的技术方案的步骤是:For achieving the above object, the steps of the technical solution adopted in the present invention are:

步骤一、将30~35wt%的莫来石颗粒、20~25wt%的莫来石细粉、30~35wt%的堇青石颗粒、4~7wt%的糊精和5~7wt%的广西白泥置于混料机中,搅拌1~1.2h,得混合料A。Step 1, mix 30-35wt% mullite particles, 20-25wt% mullite fine powder, 30-35wt% cordierite particles, 4-7wt% dextrin and 5-7wt% Guangxi white mud Place in a mixer and stir for 1-1.2 hours to obtain Mixture A.

步骤二、将30~35wt%的莫来石细粉、30~35wt%的镁铝尖晶石细粉和35~36wt%的红柱石细粉置于混料机中,搅拌1~1.2h,于100~110℃条件下烘干1~2h,研磨至粒度≤0.048mm,得到混合料B。Step 2. Put 30-35wt% mullite fine powder, 30-35wt% magnesium-aluminum spinel fine powder and 35-36wt% andalusite fine powder in a mixer, stir for 1-1.2h, Dry at 100-110°C for 1-2 hours, grind until the particle size is ≤0.048mm, and obtain the mixture B.

步骤三、先将所述混合料A置于模具中,再于压头表面均匀洒一层混合料B,以钵口朝下的方式在120~160MPa的条件下机压成型,然后在100~110℃条件下干燥20~24h,于1300~1400℃条件下保温5~6小时,制得莫来石-堇青石质锂电池正极材料烧结用匣钵。Step 3: Put the mixture A in the mold first, then evenly sprinkle a layer of mixture B on the surface of the pressure head, and machine press it under the condition of 120-160 MPa with the mouth of the bowl facing down, and then press it at 100-100 MPa. drying at 110°C for 20 to 24 hours, and holding at 1300 to 1400°C for 5 to 6 hours to prepare a sagger for sintering the mullite-cordierite lithium battery cathode material.

所述莫来石颗粒的化学成分是:Al2O3≥67.3wt%,SiO2≥30.4wt%,Fe2O3≥0.92wt%;所述莫来石颗粒的密度为2.82~2.97g/cm3,莫来石颗粒的粒度≤3mm。The chemical composition of the mullite particles is: Al 2 O 3 ≥ 67.3wt%, SiO 2 ≥ 30.4wt%, Fe 2 O 3 ≥ 0.92wt%; the density of the mullite particles is 2.82-2.97g/ cm 3 , the particle size of mullite particles is ≤3mm.

所述莫来石细粉包括步骤一所述莫来石细粉和步骤二所述莫来石细粉。所述莫来石细粉的化学成分是:Al2O3≥67.3wt%,SiO2≥30.4wt%,Fe2O3≥0.92wt%;所述莫来石细粉的密度为2.82~2.97g/cm3,莫来石细粉的粒度≤0.088mm。The mullite fine powder includes the mullite fine powder described in step 1 and the mullite fine powder described in step 2. The chemical composition of the mullite fine powder is: Al 2 O 3 ≥ 67.3 wt%, SiO 2 ≥ 30.4 wt%, Fe 2 O 3 ≥ 0.92 wt%; the density of the mullite fine powder is 2.82-2.97 g/cm 3 , the particle size of mullite fine powder is ≤0.088mm.

所述堇青石颗粒的化学成分是:Al2O3≥34.1wt%,SiO2≥42.2wt%,MgO≥14.3wt%;所述堇青石颗粒的密度为2.67~2.79g/cm3,堇青石颗粒的粒度≤3mm。The chemical composition of the cordierite particles is: Al 2 O 3 ≥ 34.1wt%, SiO 2 ≥ 42.2wt%, MgO ≥ 14.3wt%; the density of the cordierite particles is 2.67-2.79g/cm 3 , cordierite The particle size of the particles is ≤3mm.

所述糊精的粒度≤0.088mm。The particle size of the dextrin is ≤0.088mm.

所述广西白泥的化学成分是:Al2O3≥35.2wt%,SiO2含≥48.1wt%,K2O≥2.1wt%;所述广西白泥的粒度≤0.088mm。The chemical composition of the Guangxi white mud is: Al 2 O 3 ≥ 35.2 wt%, SiO 2 content ≥ 48.1 wt%, K 2 O ≥ 2.1 wt%; the particle size of the Guangxi white mud is ≤ 0.088mm.

所述镁铝尖晶石细粉的化学成分:MgO含量≥46.3wt%,Al2O3含量≥46.2wt%;所述镁铝尖晶石细粉的粒度≤0.088mm。The chemical composition of the magnesium aluminum spinel fine powder: MgO content≥46.3wt%, Al2O3 content≥46.2wt %; the particle size of the magnesium aluminum spinel fine powder≤0.088mm.

所述红柱石细粉的化学成分是:Al2O3≥61.8wt%,SiO2≥29.7;所述红柱石细粉的粒度≤0.088mm。The chemical composition of the andalusite fine powder is: Al 2 O 3 ≥ 61.8 wt%, SiO 2 ≥ 29.7; the particle size of the andalusite fine powder ≤ 0.088mm.

由于采用上述技术方案,本发明与现有技术相比具有以下优点:Owing to adopting above-mentioned technical scheme, the present invention has following advantage compared with prior art:

1、本发明将所制备的混合料A置于模具中,于压头表面洒有一层制备的混合料B,钵口朝下的方式机压成型,经干燥和烧成,制得莫来石-堇青石质锂电池正极材料烧结用匣钵(以下简称“匣钵”),故工艺简单;在烧成过程中在匣钵的内表面形成致密保护层,增加了匣钵的抗侵蚀性能,提高了匣钵的使用寿命。1. In the present invention, the prepared mixture A is placed in a mould, and a layer of the prepared mixture B is sprinkled on the surface of the pressure head, and the mouth of the bowl is machine pressed into shape, and dried and fired to obtain mullite - The sagger for cordierite lithium battery positive electrode material sintering (hereinafter referred to as "sagger"), so the process is simple; during the firing process, a dense protective layer is formed on the inner surface of the sagger, which increases the corrosion resistance of the sagger, Increased the service life of the sagger.

2、本发明以堇青石颗粒为骨料,由于堇青石颗粒的晶体结构使其抗热震性好,因此,所制备的匣钵具有优异的抗热震性能。2. In the present invention, cordierite particles are used as the aggregate, and the crystal structure of the cordierite particles has good thermal shock resistance, so the prepared sagger has excellent thermal shock resistance.

3本发明的原料来源丰富且成本低廉,在制备匣钵的过程中无特殊设备要求,制备与烧成时间短,故成本低和易于工业化生产。3. The raw materials of the present invention are rich in sources and low in cost. There is no special equipment requirement in the process of preparing the sagger, and the preparation and firing time is short, so the cost is low and industrial production is easy.

本发明所制备的莫来石-堇青石质锂电池正极材料烧结用匣钵经检测:成品率为99.6~99.9%;显气孔率为8.4~10.4g·cm3;体积密度为2.86~3.26g·cm3;抗折强度为10.2~13.2MPa;耐压强度为42.42~48.47MPa;900℃静态坩埚法抗渣实验侵蚀指数为2.2~3.7%。The mullite-cordierite lithium battery anode material sintering sagger prepared by the present invention is tested: the yield is 99.6-99.9%; the apparent porosity is 8.4-10.4 g·cm 3 ; the bulk density is 2.86-3.26 g ·cm 3 ; the flexural strength is 10.2-13.2MPa; the compressive strength is 42.42-48.47MPa; the erosion index of the slag-resistant test by the static crucible method at 900°C is 2.2-3.7%.

因此,本发明具有成本低廉、工艺简单和成品率高的特点;所制备的莫来石-堇青石质锂电池正极材料烧结用匣钵体积密度大、耐压强度高、抗热震性优良和抗侵蚀性能好。Therefore, the present invention has the characteristics of low cost, simple process and high yield; the prepared mullite-cordierite lithium battery positive electrode material sintering sagger has a large volume density, high compressive strength, excellent thermal shock resistance and Good corrosion resistance.

具体实施方式Detailed ways

下面结合具体实施方式对本发明作进一步的描述,并非对其保护范围的限制。The present invention will be further described below in combination with specific embodiments, which are not intended to limit the scope of protection thereof.

为避免重复,先将本具体实施方式所涉及的物料统一描述如下,实施例中不再赘述:In order to avoid duplication, the materials involved in this specific embodiment are first described in a unified manner as follows, and will not be repeated in the embodiments:

所述莫来石颗粒的化学成分是:Al2O3≥67.3wt%,SiO2≥30.4wt%,Fe2O3≥0.92wt%;所述莫来石颗粒的密度为2.82~2.97g/cm3,莫来石颗粒的粒度≤3mm。The chemical composition of the mullite particles is: Al 2 O 3 ≥ 67.3wt%, SiO 2 ≥ 30.4wt%, Fe 2 O 3 ≥ 0.92wt%; the density of the mullite particles is 2.82-2.97g/ cm 3 , the particle size of mullite particles is ≤3mm.

所述莫来石细粉包括步骤一所述莫来石细粉和步骤二所述莫来石细粉。所述莫来石细粉的化学成分是:Al2O3≥67.3wt%,SiO2≥30.4wt%,Fe2O3≥0.92wt%;所述莫来石细粉的密度为2.82~2.97g/cm3,莫来石细粉的粒度≤0.088mm。The mullite fine powder includes the mullite fine powder described in step 1 and the mullite fine powder described in step 2. The chemical composition of the mullite fine powder is: Al 2 O 3 ≥ 67.3 wt%, SiO 2 ≥ 30.4 wt%, Fe 2 O 3 ≥ 0.92 wt%; the density of the mullite fine powder is 2.82-2.97 g/cm 3 , the particle size of mullite fine powder is ≤0.088mm.

所述堇青石颗粒的化学成分是:Al2O3≥34.1wt%,SiO2≥42.2wt%,MgO≥14.3wt%;所述堇青石颗粒的密度为2.67~2.79g/cm3,堇青石颗粒的粒度≤3mm。The chemical composition of the cordierite particles is: Al 2 O 3 ≥ 34.1wt%, SiO 2 ≥ 42.2wt%, MgO ≥ 14.3wt%; the density of the cordierite particles is 2.67-2.79g/cm 3 , cordierite The particle size of the particles is ≤3mm.

所述糊精的粒度≤0.088mm。The particle size of the dextrin is ≤0.088mm.

所述广西白泥的化学成分是:Al2O3≥35.2wt%,SiO2含≥48.1wt%,K2O≥2.1wt%;所述广西白泥的粒度≤0.088mm。The chemical composition of the Guangxi white mud is: Al 2 O 3 ≥ 35.2 wt%, SiO 2 content ≥ 48.1 wt%, K 2 O ≥ 2.1 wt%; the particle size of the Guangxi white mud is ≤ 0.088mm.

所述镁铝尖晶石细粉的化学成分:MgO含量≥46.3wt%,Al2O3含量≥46.2wt%;所述镁铝尖晶石细粉的粒度≤0.088mm。The chemical composition of the magnesium aluminum spinel fine powder: MgO content≥46.3wt%, Al2O3 content≥46.2wt %; the particle size of the magnesium aluminum spinel fine powder≤0.088mm.

所述红柱石细粉的化学成分是:Al2O3≥61.8wt%,SiO2≥29.7;所述红柱石细粉的粒度≤0.088mm。The chemical composition of the andalusite fine powder is: Al 2 O 3 ≥ 61.8 wt%, SiO 2 ≥ 29.7; the particle size of the andalusite fine powder ≤ 0.088mm.

实施1Implementation 1

一种莫来石-堇青石质锂电池正极材料烧结用匣钵及其制备方法。本实施例所述制备方法是:A mullite-cordierite lithium battery cathode material sintering sagger and a preparation method thereof. The preparation method described in this embodiment is:

步骤一、将30~32wt%的莫来石颗粒、20~22wt%的莫来石细粉、33~35wt%的堇青石颗粒、4~7wt%的糊精和5~7wt%的广西白泥置于混料机中,搅拌1~1.2h,得混合料A。Step 1. Mix 30-32wt% mullite particles, 20-22wt% mullite fine powder, 33-35wt% cordierite particles, 4-7wt% dextrin and 5-7wt% Guangxi white mud Place in a mixer and stir for 1-1.2 hours to obtain Mixture A.

步骤二、将30~32wt%的莫来石细粉、33~35wt%的镁铝尖晶石细粉和35~36wt%的红柱石细粉置于混料机中,搅拌1~1.2h,于100~110℃条件下烘干1~2h,研磨至粒度≤0.048mm,得到混合料B。Step 2. Put 30-32wt% mullite fine powder, 33-35wt% magnesium-aluminum spinel fine powder and 35-36wt% andalusite fine powder in a mixer, stir for 1-1.2h, Dry at 100-110°C for 1-2 hours, grind until the particle size is ≤0.048mm, and obtain the mixture B.

步骤三、先将所述混合料A置于模具中,再于压头表面均匀洒一层混合料B,以钵口朝下的方式在120~130MPa的条件下机压成型,然后在100~110℃条件下干燥20~24h,于1300~1325℃条件下保温5~6小时,制得莫来石-堇青石质锂电池正极材料烧结用匣钵。Step 3: Put the mixture A in the mold first, then evenly sprinkle a layer of mixture B on the surface of the pressure head, and machine press it under the condition of 120-130MPa with the mouth of the bowl facing down, and then press it under the condition of 100-100MPa. Dry at 110°C for 20 to 24 hours, and heat at 1300 to 1325°C for 5 to 6 hours to prepare a sagger for sintering the mullite-cordierite lithium battery cathode material.

实施2Implementation 2

一种莫来石-堇青石质锂电池正极材料烧结用匣钵及其制备方法。本实施例所述制备方法是:A mullite-cordierite lithium battery cathode material sintering sagger and a preparation method thereof. The preparation method described in this embodiment is:

步骤一、将31~33wt%的莫来石颗粒、21~23wt%的莫来石细粉、32~34t%的堇青石颗粒、4~7wt%的糊精和5~7wt%的广西白泥置于混料机中,搅拌1~1.2h,得混合料A。Step 1. Mix 31-33wt% mullite particles, 21-23wt% mullite fine powder, 32-34t% cordierite particles, 4-7wt% dextrin and 5-7wt% Guangxi white mud Place in a mixer and stir for 1-1.2 hours to obtain Mixture A.

步骤二、将31~33wt%的莫来石细粉、32~34wt%的镁铝尖晶石细粉和35~36wt%的红柱石细粉置于混料机中,搅拌1~1.2h,于100~110℃条件下烘干1~2h,研磨至粒度≤0.048mm,得到混合料B。Step 2. Put 31-33wt% mullite fine powder, 32-34wt% magnesium-aluminum spinel fine powder and 35-36wt% andalusite fine powder in a mixer, stir for 1-1.2h, Dry at 100-110°C for 1-2 hours, grind until the particle size is ≤0.048mm, and obtain the mixture B.

步骤三、先将所述混合料A置于模具中,再于压头表面均匀洒一层混合料B,以钵口朝下的方式在130~140MPa的条件下机压成型,然后在100~110℃条件下干燥20~24h,于1325~1350℃条件下保温5~6小时,制得莫来石-堇青石质锂电池正极材料烧结用匣钵。Step 3: first place the mixture A in the mold, then evenly sprinkle a layer of mixture B on the surface of the pressure head, and machine press it under the condition of 130-140 MPa with the mouth of the bowl facing down, and then press it at 100-100 MPa. drying at 110° C. for 20 to 24 hours, and holding at 1325 to 1350° C. for 5 to 6 hours to prepare a sagger for sintering the mullite-cordierite lithium battery cathode material.

实施3Implementation 3

一种莫来石-堇青石质锂电池正极材料烧结用匣钵及其制备方法。本实施例所述制备方法是:A mullite-cordierite lithium battery cathode material sintering sagger and a preparation method thereof. The preparation method described in this embodiment is:

步骤一、将32~34wt%的莫来石颗粒、22~24wt%的莫来石细粉、31~33wt%的堇青石颗粒、4~7wt%的糊精和5~7wt%的广西白泥置于混料机中,搅拌1~1.2h,得混合料A。Step 1. Mix 32-34wt% mullite particles, 22-24wt% mullite fine powder, 31-33wt% cordierite particles, 4-7wt% dextrin and 5-7wt% Guangxi white mud Place in a mixer and stir for 1-1.2 hours to obtain Mixture A.

步骤二、将32~34wt%的莫来石细粉、31~33wt%的镁铝尖晶石细粉和35~36wt%的红柱石细粉置于混料机中,搅拌1~1.2h,于100~110℃条件下烘干1~2h,研磨至粒度≤0.048mm,得到混合料B。Step 2. Put 32-34wt% mullite fine powder, 31-33wt% magnesium-aluminum spinel fine powder and 35-36wt% andalusite fine powder in a mixer, stir for 1-1.2h, Dry at 100-110°C for 1-2 hours, grind until the particle size is ≤0.048mm, and obtain the mixture B.

步骤三、先将所述混合料A置于模具中,再于压头表面均匀洒一层混合料B,以钵口朝下的方式在140~150MPa的条件下机压成型,然后在100~110℃条件下干燥20~24h,于1350~1375℃条件下保温5~6小时,制得莫来石-堇青石质锂电池正极材料烧结用匣钵。Step 3: first place the mixture A in the mold, then evenly sprinkle a layer of mixture B on the surface of the pressure head, and machine press it under the condition of 140-150 MPa with the mouth of the bowl facing down, and then press it at 100-100 MPa. Drying at 110°C for 20-24 hours, and heat preservation at 1350-1375°C for 5-6 hours to prepare a sagger for sintering the mullite-cordierite lithium battery cathode material.

实施4Implementation 4

一种莫来石-堇青石质锂电池正极材料烧结用匣钵及其制备方法。本实施例所述制备方法是:A mullite-cordierite lithium battery cathode material sintering sagger and a preparation method thereof. The preparation method described in this embodiment is:

步骤一、将33~35wt%的莫来石颗粒、23~25wt%的莫来石细粉、30~32wt%的堇青石颗粒、4~7wt%的糊精和5~7wt%的广西白泥置于混料机中,搅拌1~1.2h,得混合料A。Step 1. Mix 33-35wt% mullite particles, 23-25wt% mullite fine powder, 30-32wt% cordierite particles, 4-7wt% dextrin and 5-7wt% Guangxi white mud Place in a mixer and stir for 1-1.2 hours to obtain Mixture A.

步骤二、将33~35wt%的莫来石细粉、30~32wt%的镁铝尖晶石细粉和35~36wt%的红柱石细粉置于混料机中,搅拌1~1.2h,于100~110℃条件下烘干1~2h,研磨至粒度≤0.048mm,得到混合料B。Step 2. Put 33-35wt% mullite fine powder, 30-32wt% magnesium-aluminum spinel fine powder and 35-36wt% andalusite fine powder in a mixer, stir for 1-1.2h, Dry at 100-110°C for 1-2 hours, grind until the particle size is ≤0.048mm, and obtain the mixture B.

步骤三、先将所述混合料A置于模具中,再于压头表面均匀洒一层混合料B,以钵口朝下的方式在150~160MPa的条件下机压成型,然后在100~110℃条件下干燥20~24h,于1375~1400℃条件下保温5~6小时,制得莫来石-堇青石质锂电池正极材料烧结用匣钵。Step 3: Put the mixture A in the mold first, then evenly sprinkle a layer of mixture B on the surface of the pressure head, and machine press it under the condition of 150-160 MPa with the mouth of the bowl facing down, and then press it at 100-100 MPa. Dry at 110°C for 20-24 hours, and keep warm at 1375-1400°C for 5-6 hours to prepare a sagger for sintering the mullite-cordierite lithium battery cathode material.

本具体实施方式与现有技术相比具有以下优点:Compared with the prior art, this specific embodiment has the following advantages:

1、本具体实施方式将所制备的混合料A置于模具中,于压头表面洒有一层制备的混合料B,钵口朝下的方式机压成型,经干燥和烧成,制得莫来石-堇青石质锂电池正极材料烧结用匣钵(以下简称“匣钵”),故工艺简单;在烧成过程中在匣钵的内表面形成致密保护层,增加了匣钵的抗侵蚀性能,提高了匣钵的使用寿命。1. In this specific embodiment, the prepared mixture A is placed in a mould, and a layer of prepared mixture B is sprinkled on the surface of the pressure head, and the mouth of the bowl is machine pressed into shape, and dried and fired to obtain Mo Lithium-cordierite lithium battery positive electrode material sintering sagger (hereinafter referred to as "saggar"), so the process is simple; during the firing process, a dense protective layer is formed on the inner surface of the sagger, which increases the corrosion resistance of the sagger Performance, improve the service life of the sagger.

2、本具体实施方式以堇青石颗粒为骨料,由于堇青石颗粒的晶体结构使其抗热震性好,因此,所制备的匣钵具有优异的抗热震性能。2. In this specific embodiment, cordierite particles are used as the aggregate, and the crystal structure of the cordierite particles has good thermal shock resistance, so the prepared sagger has excellent thermal shock resistance.

3本具体实施方式的原料来源丰富且成本低廉,在制备匣钵的过程中无特殊设备要求,制备与烧成时间短,故成本低和易于工业化生产。3. The source of raw materials in this specific embodiment is abundant and the cost is low. There is no special equipment requirement in the process of preparing the sagger, and the preparation and firing time is short, so the cost is low and industrial production is easy.

本具体实施方式所制备的莫来石-堇青石质锂电池正极材料烧结用匣钵经检测:成品率为99.6~99.9%;显气孔率为8.4~10.4g·cm3;体积密度为2.86~3.26g·cm3;抗折强度为10.2~13.2MPa;耐压强度为42.42~48.47MPa;900℃静态坩埚法抗渣实验侵蚀指数为2.2~3.7%。The sagger for sintering the mullite-cordierite lithium battery positive electrode material prepared in this specific embodiment is tested: the yield rate is 99.6-99.9%; the apparent porosity is 8.4-10.4 g·cm 3 ; the bulk density is 2.86- 3.26g·cm 3 ; flexural strength is 10.2-13.2MPa; compressive strength is 42.42-48.47MPa; 900℃ static crucible method slag resistance test erosion index is 2.2-3.7%.

因此,本具体实施方式具有成本低廉、工艺简单和成品率高的特点;所制备的莫来石-堇青石质锂电池正极材料烧结用匣钵体积密度大、耐压强度高、抗热震性优良和抗侵蚀性能好。Therefore, this specific embodiment has the characteristics of low cost, simple process and high yield; the prepared mullite-cordierite lithium battery positive electrode material sintering sagger has a large volume density, high compressive strength, and thermal shock resistance Excellent and good corrosion resistance.

Claims (9)

1.一种莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法,其特征在于所述制备方法的具体步骤是:1. A preparation method of a mullite-cordierite lithium battery cathode material sintering sagger, characterized in that the specific steps of the preparation method are: 步骤一、将30~35wt%的莫来石颗粒、20~25wt%的莫来石细粉、30~35wt%的堇青石颗粒、4~7wt%的糊精和5~7wt%的广西白泥置于混料机中,搅拌1~1.2h,得混合料A;Step 1, mix 30-35wt% mullite particles, 20-25wt% mullite fine powder, 30-35wt% cordierite particles, 4-7wt% dextrin and 5-7wt% Guangxi white mud Place in a mixer and stir for 1-1.2 hours to obtain Mixture A; 步骤二、将30~35wt%的莫来石细粉、30~35wt%的镁铝尖晶石细粉和35~36wt%的红柱石细粉置于混料机中,搅拌1~1.2h,于100~110℃条件下烘干1~2h,研磨至粒度≤0.048mm,得到混合料B;Step 2. Put 30-35wt% mullite fine powder, 30-35wt% magnesium-aluminum spinel fine powder and 35-36wt% andalusite fine powder in a mixer, stir for 1-1.2h, Dry at 100-110°C for 1-2 hours, grind until the particle size is ≤0.048mm, and obtain the mixture B; 步骤三、先将所述混合料A置于模具中,再于压头表面均匀洒一层混合料B,以钵口朝下的方式在120~160MPa的条件下机压成型,然后在100~110℃条件下干燥20~24h,于1300~1400℃条件下保温5~6小时,制得莫来石-堇青石质锂电池正极材料烧结用匣钵。Step 3: Put the mixture A in the mold first, then evenly sprinkle a layer of mixture B on the surface of the pressure head, and machine press it under the condition of 120-160 MPa with the mouth of the bowl facing down, and then press it at 100-100 MPa. drying at 110°C for 20 to 24 hours, and holding at 1300 to 1400°C for 5 to 6 hours to prepare a sagger for sintering the mullite-cordierite lithium battery cathode material. 2.根据权利要求1所述的莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法,其特征在于所述莫来石颗粒的化学成分是:Al2O3≥67.3wt%,SiO2≥30.4wt%,Fe2O3≥0.92wt%;所述莫来石颗粒的密度为2.82~2.97g/cm3,莫来石颗粒的粒度≤3mm。2. The preparation method of the mullite-cordierite lithium battery cathode material sintering sagger according to claim 1, characterized in that the chemical composition of the mullite particles is: Al 2 O 3 ≥ 67.3wt% , SiO 2 ≥ 30.4wt%, Fe 2 O 3 ≥ 0.92wt%; the density of the mullite particles is 2.82-2.97g/cm 3 , and the particle size of the mullite particles is ≤ 3mm. 3.根据权利要求1所述的莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法,其特征在于所述莫来石细粉的化学成分是:Al2O3≥67.3wt%,SiO2≥30.4wt%,Fe2O3≥0.92wt%;所述莫来石细粉的密度为2.82~2.97g/cm3,莫来石细粉的粒度≤0.088mm。3. The preparation method of the mullite-cordierite lithium battery anode material sintering sagger according to claim 1, characterized in that the chemical composition of the mullite fine powder is: Al 2 O 3 ≥ 67.3wt %, SiO 2 ≥ 30.4wt%, Fe 2 O 3 ≥ 0.92wt%; the density of the mullite fine powder is 2.82-2.97g/cm 3 , and the particle size of the mullite fine powder is ≤ 0.088mm. 4.根据权利要求1所述的莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法,其特征在于所述堇青石颗粒的化学成分是:Al2O3≥34.1wt%,SiO2≥42.2wt%,MgO≥14.3wt%;所述堇青石颗粒的密度为2.67~2.79g/cm3,堇青石颗粒的粒度≤3mm。4. The method for preparing the mullite-cordierite lithium battery anode material sintering sagger according to claim 1, characterized in that the chemical composition of the cordierite particles is: Al 2 O 3 ≥ 34.1wt%, SiO 2 ≥ 42.2 wt %, MgO ≥ 14.3 wt %; the density of the cordierite particles is 2.67-2.79 g/cm 3 , and the particle size of the cordierite particles is ≤ 3 mm. 5.根据权利要求1所述的莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法,其特征在于所述糊精的粒度≤0.088mm。5. The preparation method of the mullite-cordierite lithium battery anode material sintering sagger according to claim 1, characterized in that the particle size of the dextrin is ≤0.088mm. 6.根据权利要求1所述的莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法,其特征在于所述广西白泥的化学成分是:Al2O3≥35.2wt%,SiO2含≥48.1wt%,K2O≥2.1wt%;所述广西白泥的粒度≤0.088mm。6. The method for preparing the mullite-cordierite lithium battery anode material sintering sagger according to claim 1, characterized in that the chemical composition of the Guangxi white clay is: Al 2 O 3 ≥ 35.2wt%, SiO 2 content ≥ 48.1wt%, K 2 O ≥ 2.1wt%; the particle size of the Guangxi white clay ≤ 0.088mm. 7.根据权利要求1所述的莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法,其特征在于所述镁铝尖晶石细粉的化学成分:MgO含量≥46.3wt%,Al2O3含量≥46.2wt%;所述镁铝尖晶石细粉的粒度≤0.088mm。7. The preparation method of the mullite-cordierite lithium battery anode material sintering sagger according to claim 1, characterized in that the chemical composition of the magnesium aluminum spinel fine powder: MgO content ≥ 46.3wt% , Al 2 O 3 content ≥ 46.2wt%; the particle size of the magnesium aluminum spinel fine powder ≤ 0.088mm. 8.根据权利要求1所述的莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法,其特征在于所述红柱石细粉的化学成分是:Al2O3≥61.8wt%,SiO2≥29.7;所述红柱石细粉的粒度≤0.088mm。8. The preparation method of the mullite-cordierite lithium battery cathode material sintering sagger according to claim 1, characterized in that the chemical composition of the andalusite fine powder is: Al 2 O 3 ≥ 61.8wt% , SiO 2 ≥ 29.7; the particle size of the andalusite fine powder ≤ 0.088mm. 9.一种莫来石-堇青石质锂电池正极材料烧结用匣钵,其特征在于所述莫来石-堇青石质锂电池正极材料烧结用匣钵是根据权利要求1~8项中任一项所述的莫来石-堇青石质锂电池正极材料烧结用匣钵的制备方法所制备的莫来石-堇青石质锂电池正极材料烧结用匣钵。9. A mullite-cordierite lithium battery anode material sintering sagger, characterized in that the mullite-cordierite lithium battery anode material sintering sagger is according to any one of claims 1 to 8 A sagger for sintering mullite-cordierite lithium battery positive electrode materials prepared by the method for preparing a mullite-cordierite lithium battery positive electrode material.
CN201910538109.3A 2019-06-20 2019-06-20 Sagger for sintering mullite-cordierite lithium battery cathode material and preparation method thereof Pending CN110282964A (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
CN201910538109.3A CN110282964A (en) 2019-06-20 2019-06-20 Sagger for sintering mullite-cordierite lithium battery cathode material and preparation method thereof

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
CN201910538109.3A CN110282964A (en) 2019-06-20 2019-06-20 Sagger for sintering mullite-cordierite lithium battery cathode material and preparation method thereof

Publications (1)

Publication Number Publication Date
CN110282964A true CN110282964A (en) 2019-09-27

Family

ID=68004731

Family Applications (1)

Application Number Title Priority Date Filing Date
CN201910538109.3A Pending CN110282964A (en) 2019-06-20 2019-06-20 Sagger for sintering mullite-cordierite lithium battery cathode material and preparation method thereof

Country Status (1)

Country Link
CN (1) CN110282964A (en)

Cited By (18)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN112010661A (en) * 2020-09-03 2020-12-01 深圳市飞粤新材料科技有限公司 Sagger for lithium battery positive electrode material and preparation method thereof
CN112279662A (en) * 2020-11-06 2021-01-29 湘潭海泡石科技有限公司 Sagger for magnesium aluminate spinel-cordierite calcined lithium battery positive electrode material and preparation method thereof
CN112358304A (en) * 2020-11-06 2021-02-12 湘潭海泡石科技有限公司 Sagger for cordierite-magnesium aluminate spinel calcined lithium battery positive electrode material and preparation method thereof
CN112457033A (en) * 2020-11-06 2021-03-09 湘潭海泡石科技有限公司 Ceramic sagger for calcining lithium battery positive electrode material based on sepiolite mineral and preparation method thereof
CN112759377A (en) * 2021-02-07 2021-05-07 山东万乔集团有限公司 Sagger for roasting lithium battery positive electrode material and preparation method thereof
CN113200752A (en) * 2021-04-02 2021-08-03 武汉科技大学 Shaft kiln furnace lining for roasting lithium battery anode material and preparation method thereof
CN113387712A (en) * 2021-08-02 2021-09-14 湖南荣晟昌新材料科技有限公司 Sagger formula for producing ternary cathode material and production method
CN113416068A (en) * 2021-07-09 2021-09-21 阳泉银宇新材料有限责任公司 Double-layer composite structure sagger for lithium battery positive electrode material and preparation method thereof
CN113480300A (en) * 2021-07-13 2021-10-08 武汉科技大学 Mullite composite sagger and preparation method thereof
CN113773067A (en) * 2021-11-11 2021-12-10 长沙中瓷新材料科技有限公司 Sagger based on cordierite and production process thereof
CN114644525A (en) * 2022-03-04 2022-06-21 北方民族大学 Composite saggar with added waste material and preparation method thereof
CN115466128A (en) * 2022-09-27 2022-12-13 中钢集团洛阳耐火材料研究院有限公司 Sagger with titanium-containing composite layer
CN115536406A (en) * 2022-09-02 2022-12-30 洛阳欧斯特新材料有限公司 Sagger for calcining negative electrode material
CN116621591A (en) * 2023-05-17 2023-08-22 厦门中科金源新能源科技有限公司 A kind of sagger for positive electrode material of lithium battery and preparation method thereof
CN117164368A (en) * 2023-09-04 2023-12-05 格林美(无锡)能源材料有限公司 Preparation method of sagger for sintering sodium ion battery anode material
CN119241222A (en) * 2024-09-27 2025-01-03 广东山摩新材料科技有限公司 A composite structure sagger for lithium battery positive electrode material and preparation method thereof
EP4520742A4 (en) * 2022-06-07 2026-04-29 Ecopro Bm Co Ltd Fireproof mold for sintering raw material
EP4741363A1 (en) * 2024-11-11 2026-05-13 Steuler-KCH GmbH Container for cathode active materials

Citations (6)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN103884190A (en) * 2012-12-19 2014-06-25 日本精细陶瓷有限公司 Ceramic coating sagger for manufacturing lithium ion anode active material and manufacturing method thereof
CN104987094A (en) * 2015-07-08 2015-10-21 武汉理工大学 Alkali resistant ceramic coating material and preparation method thereof
CN105693227A (en) * 2016-01-08 2016-06-22 浙江长兴久鑫耐火材料有限公司 Novel saggar
CN105777090A (en) * 2016-03-21 2016-07-20 武汉理工大学 Sagger with coatings capable of resisting high-temperature lithium battery corrosion and method for preparing sagger
CN108302942A (en) * 2018-01-08 2018-07-20 朱性宇 Electrode material of lithium battery prepares the preparation method with saggar, the protective layer of the saggar and saggar
CN108585893A (en) * 2018-04-27 2018-09-28 佛山市骏美特种陶瓷有限公司 The formula and its manufacture craft of anode material of lithium battery firing saggar

Patent Citations (6)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN103884190A (en) * 2012-12-19 2014-06-25 日本精细陶瓷有限公司 Ceramic coating sagger for manufacturing lithium ion anode active material and manufacturing method thereof
CN104987094A (en) * 2015-07-08 2015-10-21 武汉理工大学 Alkali resistant ceramic coating material and preparation method thereof
CN105693227A (en) * 2016-01-08 2016-06-22 浙江长兴久鑫耐火材料有限公司 Novel saggar
CN105777090A (en) * 2016-03-21 2016-07-20 武汉理工大学 Sagger with coatings capable of resisting high-temperature lithium battery corrosion and method for preparing sagger
CN108302942A (en) * 2018-01-08 2018-07-20 朱性宇 Electrode material of lithium battery prepares the preparation method with saggar, the protective layer of the saggar and saggar
CN108585893A (en) * 2018-04-27 2018-09-28 佛山市骏美特种陶瓷有限公司 The formula and its manufacture craft of anode material of lithium battery firing saggar

Cited By (22)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN112010661A (en) * 2020-09-03 2020-12-01 深圳市飞粤新材料科技有限公司 Sagger for lithium battery positive electrode material and preparation method thereof
CN112279662A (en) * 2020-11-06 2021-01-29 湘潭海泡石科技有限公司 Sagger for magnesium aluminate spinel-cordierite calcined lithium battery positive electrode material and preparation method thereof
CN112358304A (en) * 2020-11-06 2021-02-12 湘潭海泡石科技有限公司 Sagger for cordierite-magnesium aluminate spinel calcined lithium battery positive electrode material and preparation method thereof
CN112457033A (en) * 2020-11-06 2021-03-09 湘潭海泡石科技有限公司 Ceramic sagger for calcining lithium battery positive electrode material based on sepiolite mineral and preparation method thereof
CN112759377A (en) * 2021-02-07 2021-05-07 山东万乔集团有限公司 Sagger for roasting lithium battery positive electrode material and preparation method thereof
CN113200752B (en) * 2021-04-02 2023-07-28 武汉科技大学 Shaft kiln lining for roasting lithium battery anode material and preparation method thereof
CN113200752A (en) * 2021-04-02 2021-08-03 武汉科技大学 Shaft kiln furnace lining for roasting lithium battery anode material and preparation method thereof
CN113416068A (en) * 2021-07-09 2021-09-21 阳泉银宇新材料有限责任公司 Double-layer composite structure sagger for lithium battery positive electrode material and preparation method thereof
CN113480300B (en) * 2021-07-13 2023-07-21 武汉科技大学 A kind of mullite composite sagger and its preparation method
CN113480300A (en) * 2021-07-13 2021-10-08 武汉科技大学 Mullite composite sagger and preparation method thereof
CN113387712A (en) * 2021-08-02 2021-09-14 湖南荣晟昌新材料科技有限公司 Sagger formula for producing ternary cathode material and production method
CN113773067B (en) * 2021-11-11 2022-01-18 长沙中瓷新材料科技有限公司 Sagger based on cordierite and production process thereof
CN113773067A (en) * 2021-11-11 2021-12-10 长沙中瓷新材料科技有限公司 Sagger based on cordierite and production process thereof
CN114644525A (en) * 2022-03-04 2022-06-21 北方民族大学 Composite saggar with added waste material and preparation method thereof
EP4520742A4 (en) * 2022-06-07 2026-04-29 Ecopro Bm Co Ltd Fireproof mold for sintering raw material
CN115536406A (en) * 2022-09-02 2022-12-30 洛阳欧斯特新材料有限公司 Sagger for calcining negative electrode material
CN115466128A (en) * 2022-09-27 2022-12-13 中钢集团洛阳耐火材料研究院有限公司 Sagger with titanium-containing composite layer
CN116621591A (en) * 2023-05-17 2023-08-22 厦门中科金源新能源科技有限公司 A kind of sagger for positive electrode material of lithium battery and preparation method thereof
CN117164368A (en) * 2023-09-04 2023-12-05 格林美(无锡)能源材料有限公司 Preparation method of sagger for sintering sodium ion battery anode material
CN117164368B (en) * 2023-09-04 2025-09-09 格林美(无锡)能源材料有限公司 Preparation method of sagger for sintering sodium ion battery anode material
CN119241222A (en) * 2024-09-27 2025-01-03 广东山摩新材料科技有限公司 A composite structure sagger for lithium battery positive electrode material and preparation method thereof
EP4741363A1 (en) * 2024-11-11 2026-05-13 Steuler-KCH GmbH Container for cathode active materials

Similar Documents

Publication Publication Date Title
CN109320222B (en) Preparation method of cordierite-mullite ceramic sagger
CN108516849B (en) Zirconium mullite brick for cement kiln and preparation method thereof
CN106145976B (en) Andalusite-mullite-silicon carbide brick for cement kiln and preparation method thereof
CN105669223A (en) Sagger
CN103030413B (en) Method for preparing corundum mullite crucible
CN116675544B (en) Refractory castable and preparation method thereof
CN113548884B (en) Sagger containing cordierite and composite spinel mullite and preparation method thereof
CN117142843B (en) Rotary tube for molding medium borosilicate glass tube and preparation method thereof
CN100378029C (en) A kind of porous spinel ceramic material and preparation method thereof
CN110498673A (en) A kind of mullite crystal whisker enhancing alumina hollow ball porous ceramics preparation method
CN101182231B (en) A kind of inorganic binder, preparation method and its application in the preparation of porous ceramics
CN110452007A (en) A kind of preparation method of hollow magnesium aluminum spinel whisker skeleton porous ceramics
CN110668828A (en) Magnesium binder for cement-free castable and preparation method thereof
CN108276017B (en) A kind of corundum-silicon carbide whisker composite ceramic material using natural mineral as raw material and preparation method thereof
CN106316441A (en) Porous thermal insulation ceramics made from bauxite tailings and preparation method thereof
CN104944979A (en) Preparation method of firebrick used for rotary kiln
CN110207499A (en) Anode material of lithium battery sintering saggar based on magnesium aluminate spinel colloidal sol and preparation method thereof
CN103833387B (en) High abrasion silicon mullite red brick and preparation technology thereof
CN106365654B (en) A kind of anti-lithium electric material erosion fire-clay crucible adding ZrN-SiAlON
CN117003569A (en) Chromium-zirconium corundum aggregate and preparation method thereof, chromium-zirconium corundum composite material and preparation method and application thereof
CN113754413B (en) Preparation method of special ceramic tile with high acid resistance, temperature resistance and pressure resistance
CN108083823A (en) Compound saggar, its preparation method and application
CN111393156A (en) Preparation method of cordierite porous ceramics
CN115092940A (en) Preparation method of tricalcium silicate powder
CN114736007A (en) Low-heat-conductivity high-performance aluminum-magnesia-carbon molten pool brick and preparation method thereof

Legal Events

Date Code Title Description
PB01 Publication
PB01 Publication
SE01 Entry into force of request for substantive examination
SE01 Entry into force of request for substantive examination
WD01 Invention patent application deemed withdrawn after publication
WD01 Invention patent application deemed withdrawn after publication

Application publication date: 20190927